423PEffectiveness of first-generation 5HT3 receptor antagonist plus dexamethasone plus aprepitant in controlling delayed chemotherapy-induced nausea and vomiting in patients with colorectal cancer: A propensity score-matched analysis. (24th November 2019) - Hayashi, T; Shimokawa, M; Matsuo, K; Iihara, H; Nishimura, J; Nakano, T; Egawa, T
Abstract: Background: Delayed chemotherapy-induced nausea and vomiting (CINV) is not well controlled in patients with colorectal cancer (CRC) treated with oxaliplatin (L-OHP)-based chemotherapy. Whether adding a neurokinin-1 receptor antagonist to a first-generation 5HT3 antagonist (1 st -5HT3 RA) and dexamethasone (DEX) is beneficial in patients on L-OHP-based chemotherapy is controversial. It is unclear whether palonosetron (PALO) or aprepitant (APR) is more effective in controlling delayed CINV. We, therefore, investigated whether PALO+DEX (PALO group) or 1 st -5HT3 RA+DEX+APR (APR group) was more effective in controlling delayed CINV, as well as risk factors for delayed CINV, in patients with CRC treated with L-OHP-based chemotherapy. Methods: We pooled data from two prospective observational studies in Japan and one phase III clinical trial and compared the incidence of CINV between the PALO and APR groups using propensity score-matched analysis. Risk factors for CINV were identified using logistic regression models. Results: Among the 404 eligible patients, those in the PALO group showed a higher incidence of delayed CINV than those in the APR group (nausea: 43.4% vs. 32.4%, P = 0.061; vomiting: 12.5% vs. 4.4%, P = 0.017). The logistic regression analysis identified alcohol consumption, motion sickness, and PALO+DEX regimen as independent risk factors for delayed nausea, and female sex and PALO+DEX regimen as those for delayed vomiting. Conclusions: Treatment with the three antiemetics, including APR, was more effective in controlling delayed CINV than prophylactic treatment with the two antiemetics, including PALO. Thus, patients with CRC receiving L-OHP-based chemotherapy should be treated with three antiemetics, including APR. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.